Field-Based Experiential Education in Geography: Discovering and Rethinking Urban Environmental Challenges and Possibilities. Issue 2 (4th March 2021) - MacKay, Carley; Tran, Kim; Lunstrum, Elizabeth
Abstract: Drawing on our experience teaching a 2-week field-based geography course on urban environmental issues, we reinforce the value of field-based experiential education (EE) especially as it faces growing threats. We show how such experience can enable students to understand the diversity of urban environmental challenges in situ; grasp cities as sites of environmental sustainability; understand the innovative ways local organizations and actors – many of them Black, Indigenous, and People of Color – are addressing these challenges; and feel empowered to take part in environmental stewardship. Focusing on course design and delivery, we additionally offer a blueprint for course replicability.